The Effect of Spirit Gate Acupressure Therapy on Sleep Quality in Premenopausal Women in Banjar Gambang, Munggu Village - Anggreni, Ni Putu Ayu Dian; Widiastini, Luh Putu; Adhiestiani, Ni Made Egar (Jurnal Kesehatan Pasak Bumi Kalimantan, 2024)
The degradation in sleep quality has been occur by around 20%-50% in adults in Indonesia. Women experience this incidence more frequently in the age group above 40 years. As many as 54% of premenopausal women complain about poor sleep quality. One of the efforts that can be made to address sleep disorders is complementary therapy, namely acupressure therapy. The objective of this study is to determine the influence of Spirit Gate acupressure therapy on sleep quality in premenopausal women in Banjar Gambang, Munggu Village. The research design is Quasi-Experimental Design using the Non-Equivalent Control Group Design approach. The total sample consists of 30 respondents, comprising 15 respondents in the control group and 15 respondents in the treatment group of premenopausal women in Banjar Gambang, Munggu Village, selected using purposive sampling technique. The data is analyzed using Mann-Whitney analysis. Based on the results of the data analysis, the average post-test score for the treatment group is 4.27, which is less than the control group's 9.07, with a mean difference of 4.8. This means that the average sleep quality score for the treatment group falls into the good category, while the control group falls into the poor category. The p-value is 0.001, which is less than 0.05. Therefore, H0 is rejected, and Ha is accepted. It can be concluded that there is an influence of Spirit Gate acupressure therapy on sleep quality in premenopausal women in Banjar Gambang, Munggu Village.